MENUJU ERA AKTIVISME DIGITAL (Agenda Setting Media Informasi Kota Semarang Dalam Mengadvokasi Kasus Kekerasan Terhadap Pekerja Rummah Tangga) - Muhammad - Kholilurrohman; Wijayanto - -; Hendra Try Ardianto (Journal of Politic and Government Studies, 2021)
The presence of the internet and social media has a huge impact on people's attitudes and behavior. Media Informasi Kota Semarang (MIK Semar) is an example of how the harmony of community activities (real and virtual) is tested when faced with cases of violence that occur around them. This research explicitly aims to look at digital activism carried out by the Media Informasi Kota Semarang (MIK Semar) based on agenda setting theory. Media Informasi Kota Semarang (MIK Semar) as a social media group that has been established in various social activities replaces the role of mass media in raising the issue to the pu blic. Media Informasi Kota Semarang (MIK Semar) has successfully used social media as a starting point for a movement to help victims of violence so that it is able to influence government policy in viewing the case. Through McCombs and Shaw's agenda setting theory, this research reveals how digital activism can transform into the real world and its implications for solving the cases it handles. The results of this study indicate that the Media Informasi Kota Semarang (MIK Semar) has a major role in solving one of the cases of violence involving domestic workers. Media Informasi Kota Semarang (MIK Semar) became the accelerator for the resolution of the case by taking the initiative to accumulate social support from netizens through social media. This social support is then transformed into the real world in the form of providing legal assistance by the Team Media Informasi Kota Semarang (MIK Semar) to the victims.